Impact of Bioameliorants and Trichoderma sp. on Nutrient Availability, Plant Immunity, and Red Chili Productivity. - Fathya Dewi Amalia (Jurnal Online Pertanian Tropik, 2025)
The low productivity of chili plants needs to be increased through soil fertility and pest and disease control. The application of bioameliorants (50% biochar, 25% sugarcane blotong compost, 10% dolomite, 10% guano, 2.5% humic acid, and 2.5% biofertilizer) aims to improve the physical, chemical, and biological properties of the soil and enhance nutrient availability. Trichoderma sp. is needed to stimulate growth and induce resistance. The research aims to determine the best interaction and dosage of bioameliorants and Trichoderma sp. on the parameters of phosphate-solubilizing bacteria, available P, plant height, number of leaves, fruit weight, number of fruits per plant, and induced resistance. The research was conducted at the Bale Tatanen Experimental Garden of the Faculty of Agriculture, Universitas Padjadjaran. The research used a Randomized Block Design (RBD) factorial with nine treatments and three repetitions. The treatments included bioameliorants at 0 t ha-1, 3 t ha-1, 6 t ha-1 and Trichoderma sp. at 0 kg ha-1, 8 kg ha-1, and 16 kg ha-1. The results of the application of bioameliorants and the biological agent Trichoderma sp., as well as the control treatment, showed no interaction between treatments. The application of bioameliorants and biological agents showed the best dose in the independent effect of bioameliorant at 6 t ha-1, which increased available P by 86.6% compared to the control. The application of Trichoderma sp. showed the best dose at 16 kg ha-1, which reduced the intensity of leaf curl virus disease by 66.6% compared to the control and reduced the intensity of fruit fly pest attacks at 16 kg ha-1 by 20.5% compared to the control.